Diagnostics of abnormal personality (psychopathy) - Jakubik, Andrzej (Studia Psychologica: Theoria et praxis, 2006)
The main subject of the paper is the presentation of the diagnostics of psychopathy from the point of view of contemporary psychopathology. In this review of the literature, the author reports on basic assumptions for personality structure disorders. At the beginning, this work concerns history of the field, development of the conception of psychopathy, definition of different terms (abnormal personality, antisocial personality, dissocial personality etc.) and a map of the problems to be approached. Successively, the paper focuses on clinical diagnostic criteria of abnormal personality. Finally, the author presents diagnostic controversies about the relationship between alcoholism or narcotic addiction and psychopatic personality.